The Anaphase Promoting Complex/Cyclosome Subunit 11 and Its Role in Organ Size and Plant Development - Schwedersky, Rodrigo Porto; Saleme, Marina de Lyra Soriano; Rocha, Ingrid Andrade; Montessoro, Patricia da Fonseca; Hemerly, Adriana Silva; Eloy, Nubia Barbosa; Ferreira, Paulo Cavalcanti Gomes (Frontiers in Plant Science, 2021)
The Anaphase Promoting Complex/Cyclosome (APC/C), a member of the E3 ubiquitin ligase family, plays an important role in recognizing the substrates to be ubiquitylated. Progression of anaphase, and therefore, of the cell cycle, is coordinated through cyclin degradation cycles dependent of proteolysis triggered by APC/C. The APC/C activity depends on the formation of a pocket comprising the catalytic subunits APC2, APC11 and APC10. Among these, the role of APC11 outside the cell division cycle is poorly understood. Therefore, the goal of this work was to analyze the function of APC11 during plant development by characterizing apc11 knock-down mutant lines. Accordingly, we observed decreased APC11 expression in the mutant lines, followed by a reduction on meristem root size based on the cortical cell length, and an overall size diminishment throughout development. Additionally, crosses of apc11-1 and amiR-apc11 with plants carrying a WUSCHEL-RELATED HOMEOBOX5 fluorescent marker showed a weakening of the GFP-positive cells in the Quiescent Center. Moreover, apc11-1 plants show a decreased leaf area together with a decrease in cell area when shoot development was observed by kinematics analysis. Finally, we observed a decreased APC/C activity in the root and shoot meristems in crosses of pCYCB1;1:D-box-GUS with apc11-1 plants. Our results indicate that APC11 is important in the early stages of development, mediating meristematic architecture through APC/C activity affecting the overall plant growth.